Chlorinated hydrocarbons in the environment – monitoring and effect monitoring - Kettrup, A.A.F. (Актуальні проблеми транспортної медицини, 2005)
Thousands of chemicals are traded on the market, but only in a few cases is full information available on their distribution and their effects on man and the environment. In addition to real time monitoring of chemicals, it is, thus, necessary to establish an environmental specimen bank (ESB) for the retrospective monitoring of chem¬icals in the future. The base of ESB are representative bioindicators of systematically collected biological and environmental samples. As a result of extremely low storage temperature (T = < - 150°C) it is guaranteed that the samples are not subject to chemical changes during the long-term storage. Furthermore we need in addition an effect monitoring, using in vitro testing like for example P 450 1A1 enzyme expression.